Prescription Pattern in patients with Acute Tonsillitis, attending Outpatient Department - Tahir Hussain Khan, Irfan Ahmed Shaikh, Muhammad Jamil Memon, Danishur Rahim, Tariq Zia Siddiqui, Mukhtar Ibrahim, Bisma Saleem (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Acute tonsillitis is a major health problem among children and adults which is badly effects the quality of life. Aim: To determine the antimicrobial prescription pattern in patients with acute tonsillitis, attending ENT OPD of Kulsumbai Valika, Social Security, Post Graduate Teaching Hospital Karachi.. Methodology: This cross-sectional study was conducted among the patients attending the outpatient of ENT, with acute tonsillitis. Study was conducted in Outpatient of ENT department of Kulsumbai Valika Social Security S.I.T.E. Hospital, Karachi. from 1st January 2023 to 31st December 2023. Data collection was done from the prescription of each patient. Statistical analysis was carried out using SPSS version 23. Results: A total of 210 acute tonsillitis patients, with 116(55.23%) were male. Mean number of the drugs in prescription 4±1.4. All the prescriptions included antimicrobials, 185(88%), and NSAIDs. Amoxicillin / Clavulanic acid (24.8%) and Ceftriaxone (12.2%) were the most commonly prescribed antimicrobials. Parenteral route was preferred in 113(53.8%). None of the patients was offered culture or sensitivity test of the microorganisms. Practical implication: Acute tonsillitis patients admitted and started parenteral antibiotic along with anti-inflammatory drugs. Conclusion: Antimicrobials thosewere prescribed in almost all cases of acute tonsilitis, and most frequently prescribed were Amoxicillin / Clavulanic acid and Cefixime. Injectable antibiotics were also prescribed very frequently. Most of the patients were given just one antibiotic. This study findings highlighted the gaps the rational practices in drug prescribing for acute tonsilitis. Keywords: Acute tonsillitis, Amoxicillin,antimicrobials, Clavulanic acid, Cefixime, prescription.